2022
DOI: 10.1093/discim/kyac002
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D signaling regulates IL-17A-producing γδT cells in mice to promote cancer progression

Abstract: γδT cells are unconventional T cells particularly abundant in mucosal tissues that play an important role in tissue surveillance, homeostasis and cancer. γδT cells recognize stressed cells or cancer cells through the NKG2D receptor to kill these cells and maintain normality. Contrary to the well-established anti-tumor function of these NKG2D-expressing γδT cells, we show here that, in mice, NKG2D regulates a population of pro-tumor γδT cells capable of producing IL-17A. Germline deletion of Klrk1, the gene enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…To probe the requirement for NKG2D in TIL activation in this model, we used NKG2D-deficient mice on the Apc min background. We previously reported that Apc min/+ mice deficient for Klrk1 ( Apc min/ ;Klrk1 −/− ) survive longer than Apc min/+ ;Klrk1 +/+ mice and displayed a lower tumor burden [ 30 ]. When comparing the frequencies of IFNγ-producing CD8 + T cells in Apc min/+ ;Klrk1 +/+ and Apc min/+ ;Klrk1 −/− mice, we found that the frequency of CD8 + T cells was significantly decreased in the absence of NKG2D ( Figure 4 a,b) demonstrating the importance of NKG2D in CD8 + T cells enrichment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To probe the requirement for NKG2D in TIL activation in this model, we used NKG2D-deficient mice on the Apc min background. We previously reported that Apc min/+ mice deficient for Klrk1 ( Apc min/ ;Klrk1 −/− ) survive longer than Apc min/+ ;Klrk1 +/+ mice and displayed a lower tumor burden [ 30 ]. When comparing the frequencies of IFNγ-producing CD8 + T cells in Apc min/+ ;Klrk1 +/+ and Apc min/+ ;Klrk1 −/− mice, we found that the frequency of CD8 + T cells was significantly decreased in the absence of NKG2D ( Figure 4 a,b) demonstrating the importance of NKG2D in CD8 + T cells enrichment.…”
Section: Resultsmentioning
confidence: 99%
“…IFNγ is typically an indicator of good prognosis in colorectal cancer [ 37 ], yet studies have suggested that low concentrations of IFNγ can negatively impact the anti-tumor response, whereas high levels lead to tumor regression [ 38 ]. To understand the mechanism resulting in IFNγ-mediated tumor progression, we used a mouse model of colorectal cancer where we previously showed that NKG2D-deficiency improved survival [ 30 ]. We observed that T cells expanded and/or accumulated at late stages of disease in an NKG2D-dependent manner where they produced high levels of IFNγ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations